Infant and Young Child Feeding – Knowledge and Practices of ASHA workers of Doiwala Block, Dehradun District - Saxena, Vartika; Kumari, Ranjeeta (Indian Journal of Community Health, 2014)
Introduction: Promotion and support of breastfeeding is a global priority and an important child-survival intervention. Accredited Social Health Activists (ASHAs) can play a significant role in the promotion of breast-feeding. Present research paper reviews their knowledge & practices with respect to Infant and Young Child Feeding (IYCF) issues. Further, it also analyzes difficulties being faced by them in promoting positive IYCF practices so that necessary support can be provided for carrying out their desired role. Material and Methods: It was a descriptive, cross-sectional study conducted in the block Doiwala of Dehradun district, Uttarakhand. All 168 ASHAs were included in the study for the assessment of knowledge and practices by interview technique based on predesigned and pre-tested questionnaire. Results: 98% ASHAs had complete and correct information about exclusive breast feeding, however only 38% ASHAs were aware that breastfeeding should be started within 4 hours in children delivered by caesarean section. Only 18% ASHAs reported to be able to motivate mothers to practice exclusive breast feeding. Insufficient mother’s milk (55.4%), Caesarean sections (20.2%), coercion from elders in the family to start top milk were among the important factors attributed for failure of exclusive breastfeeding. Regarding complementary feeding, only 45% ASHAs knew the correct timing of initiation of complementary feeding; however 58% ASHAs had introduced the complementary feeding at 7th month in their children. 83.9% ASHAs knew that complementary food should be semisolid in consistency, while 87.5% and 32.7% ASHAs were aware that egg and non-vegetarian food items can be given as complementary food to the child. Bottle feeding had been practiced by about 33% of ASHAs in the past; however no ASHA had reported bottle feeding currently. Conclusion: Present research paper concludes that although knowledge level of ASHAs is high regarding IYCF practices but it does not match with the actual practices. They require skill building especially in the area of breastfeeding options for working women as well as complementary feeding.